Character Education Values in the Process of Mathematical Problem-Solving, Understanding, Connection and Communication: Students’ Perspectives - Nurhayati, Suci; Asria, Vingky Zulfa; Yunianika, Ika Tri (IndoMath: Indonesia Mathematics Education, 2024)
The purpose of this study is to describe students' perceptions of character values that are integrated into each activity of Mathematical Power, which consists of problem-solving, understanding, connecting, and communication. This qualitative research collected data with a survey of students about their perceptions and interviews with mathematics teachers. The sample of schools were selected based on the types of schools: faith-based school and non-faith-based school located in Yogyakarta city. From the four selected schools, 61 samples of grade XI students and 4 mathematics teachers in each school were involved in this study. After the data was collected, the survey data was analyzed descriptively, and the interview data was analyzed using data reduction, data collection, and conclusions. Based on the results of students’ perceptions, character values have been widely felt by most students, with the largest percentage in mathematical communication activities. Non-faith-based schools scored higher than faith-based schools in students' perceptions of character values in all four mathematical activities.